ASSOCIATION OF MAGNESIUM AND VITAMIN B6 DEFICIENCY WITH ANXIETY AND PANIC ATTACKS IN PREGNANT WOMEN DURING THE THIRD TRIMESTER: A CASE-CONTROL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Anxiety and panic attacks are common during pregnancy, particularly in the third trimester due to hormonal fluctuations and increased physiological stress. Magnesium and vitamin B6 play critical roles in neurotransmitter function and stress regulation, yet their deficiencies may contribute to heightened anxiety symptoms.Objective: To Assess the association between magnesium and Vitamin B6 Deficiency with frequency of anxiety symptoms and panic disorder in pregnancy and third trimesters.Methods: Case-control study in 200 pregnant women at third trimester age, 28–40 weeks of gestation. The population was divided into two groups consisting of 100 cases with clinical anxiety/panic attacks and 100 healthy controls. Blood was collected for estimating serum magnesium and vitamin B6. Anxiety score was measured on the Edinburgh Postnatal Depression Scale (EPDS) and the Generalized Anxiety Disorder-7 (GAD-7) scale. Food intake and supplements taken were documented. Association studies were done using statistical analyses, such as t-tests and logistic regression.Results: Pregnant women with anxiety and panic attacks had significantly lower mean serum levels of magnesium (p < 0.05) and vitamin B6 (p < 0.05) compared to the controls. The levels of magnesium and B6 were inversely correlated with the severity scores of anxiety. Deficiency in both nutrients was found to be associated with a significant risk of a panic attack (OR: 2.5, 95% CI: 1.8–3.6, p < 0.001).Conclusion: Magnesium and vitamin B6 deficiencies are significantly related to a heightened risk of anxiety and panic attacks during the third trimester of pregnancy. Nutritional intervention in this context, such as diet modification and supplementation may help mitigate such symptoms. It is recommended that researchers conduct more longitudinal studies to further establish this relationship and possibly its causality.